The Redesign of Immigration Policy for the Venezuelan Inflows in South American Countries (2017-2022) - Al Nijjar Salloum, Sandra (Migraciones. Publicación del Instituto Universitario de Estudios sobre Migraciones, 2022)
With the Venezuelan exodus, twelve Latin American countries have implemented migratory restrictions: which factors explain this redesign of immigration policies? The working hypothesis proposes that the migratory pressure of vulnerable massive inflows, will lead to the redesign of the immigration policy. The mix of instruments will restrict entry, and make the regularization component more flexible. The key conditioning factor is the anticipation of the host state’s policy capacity to absorb the migration shock. Through a comparative study including three countries, these explanatory factors are identified, studying the context and conditions that shaped the response. In Colombia, the deviant case, the cost-benefit analysis between border restriction and migratory integration explain the openness. In Ecuador, the transformation of its migratory profile and the anticipation of its policy capacity, explained the migratory restrictions adopted. In Peru, ideas about the migration-development link, policy capacity forecasts, and the semi-presidential institutional structure, explained their policy decisions.